Research on the piston precise electromagnetic centering of labyrinth-piston compressor. (June 2016) - Cheng, Junming; Zhang, Meimei; Liu, Zhan; Feng, Quanke; Zeng, Xiangjun
In labyrinth piston compressor, the precise centering of the piston is the most important prerequisite to realize the labyrinth seal and ensure the compressor running safety. However, the piston suffers very large periodically varying loads caused by the gas force and the inertia force, which lead to the eccentrically running of the piston in cylinder. Under this condition, the leakage of the labyrinth piston compressor will be intensified, and the risk of the friction between piston and cylinder wall will increase. In order to realize the piston precise centering, in this paper, an electromagnetic centering system is introduced including the principle, structure, and application. In order to realize the piston precise electromagnetic centering outside of the cylinder, the through-piston rod is adopted. And the guide bearing can be removed. Thus, the current cantilever structure for the piston centering will be replaced with the simply supporting structure. More importantly, this technology can also be used for the traditional large reciprocating compressor, and thereby, the piston rings, packing and other wearing parts can be removed as well.